Mental health in ultra-endurance runners: a systematic review - Thuany, M.; Viljoen, C.; Gomes, T. N.; Knechtle, B.; Scheer, V. (Sports Medicine, 2023)
Background: Among ultra-endurance runners (UER), the mental, behavioral, and physical demands of training/competition can result in maladaptive outcomes. Mental health issues are common in athletes and can impact psychology, physical health, and performance. Objective: To synthesize information regarding the incidence/prevalence and factors associated with mental health issues among UER. Methods: Systematic searches were performed in PubMed, SPORTDiscus, Scopus, Cochrane databases, CINAHL, Web of Science, and Medline Ovid using key terms related to UER (e.g., trail running, road running) and psychological issues (e.g., exercise addiction, depression). Inclusion criteria included original articles published in peer-reviewed journals in English, using qualitative or quantitative approaches. We considered papers reporting incidence/prevalence and associated factors with mental health outcomes in UER of both sexes, all ages, and levels of competition (e.g., elite, nonprofessional runners). The Joanna Briggs Institute Analytical Cross-Sectional Studies critical appraisal tool was used for quality assessment. Results: A total of 282 studies were identified, and 11 studies were included in the final selection. A total of 3670 UER were included in the studies. The prevalence of mental health issues among UER ranged between 32.0% and 62.5% for eating disorders, from 11.5% to 18.2% for exercise addiction, 18.6% for depressive symptoms, and 24.5% for sleep disturbance. Exercise addiction was not related to weekly volume, but a strong relationship with exercise in an unstructured space, age, and body mass index was shown. Conclusion: Mental health issues among UER are common, especially eating disorders, exercise addiction, sleep disturbances, and depressive symptoms. Further high-quality studies are needed to examine underlying factors and find preventative strategies to protect UER.